Pemenuhan Hak atas Informasi Konsumen terhadap Ketidaksesuaian Harga pada Rak dengan Struk Belanja di Alfamart - Warih Pangesti Kusuma Negara; Bagya Agung Prabowo (Fakultas Hukum Universitas Islam Indonesia, 2024)
This study discusses the fulfillment of consumers' rights to information regarding discrepancies between prices on shelves and shopping receipts at Alfamart. This type of research is normative law, the approach method used is law. The source of data obtained through legal materials is in the form of primary data, namely data collection carried out through a library study basis. The results of this study are first, the right to information has not been fulfilled because business actors still tend to ignore their obligations in fulfilling consumer rights to obtain correct, honest and clear information in accordance with the condition of the goods being traded in accordance with Article 4 of Law Number 8 1999 concerning Consumer Protection. Second, business actors ignore consumer rights where when there is a difference in the price listed on the shelf and on the shopping receipt, the price on the shopping receipt is more expensive in accordance with Article 19 of Law Number 8 of 1999 concerning Consumer Protection.